Collecting and museology - Gáldy, Andrea M.; Dobmeier, Florian (Collecting histories., 2019)
To celebrate the first ten years of the international forum Collecting and Display, as well as the launch of a dedicated series of publications ""Collecting Histories"", in 2014, a conference dedicated to new directions in terms of collecting, display, visitor experience and the use of modern media in today's museums was held at museums of the city of Memmingen in Bavaria. Speakers looked into whether and how the engagement with the history of collections, in their diverse permutations, has influenced and modified modern museology. This volume looks forward towards a future which oftentimes lo.